Linkage between Neighborhood Social Cohesion and BMI of South Asians in the Masala Study - Gagandeep Gill; Nicola Lancki; Manjit Randhawa; Semran K. Mann; Adam Arechiga; Robin D. Smith; Samuel Soret; Alka M. Kanaya; Namratha Kandula (Hindawi Limited, 2020)
Introduction. South Asians in the United States have a high prevalence of obesity and an elevated risk for cardiometabolic diseases. Yet, little is known about how aspects of neighborhood environment influence cardiometabolic risk factors such as body mass index (BMI) in this rapidly growing population. We aimed to investigate the association between perceived neighborhood social cohesion and BMI among South Asians. Methods. We utilized cross-sectional data from the MASALA study, a prospective community-based cohort of 906 South Asian men and women from the San Francisco Bay area and the greater Chicago area. Multivariable linear regression models, stratified by sex, were used to examine the association between perceived level of neighborhood social cohesion and individual BMI after adjusting for sociodemographics. Results. Participants were 54% male, with an average age of 55 years, 88% had at least a bachelor's degree, and the average BMI was 26.0 kg/m2. South Asian women living in neighborhoods with the lowest social cohesion had a significantly higher BMI than women living in neighborhoods with the highest cohesion (β coefficient = 1.48, 95% CI 0.46-2.51, p=0.02); however, the association was not statistically significant after adjusting for sociodemographic factors (β coefficient = 1.06, 95% CI −0.01-2.13, p=0.05). There was no association between level of neighborhood social cohesion and BMI in South Asian men. Conclusion. Perceived neighborhood social cohesion was not significantly associated with BMI among South Asians in our study sample. Further research is recommended to explore whether other neighborhood characteristics may be associated with BMI and other health outcomes in South Asians and the mechanisms through which neighborhood may influence health.